Human orthopaedic biomechanics : fundamentals, devices and applications - Innocenti, Bernado; Galbusera, Fabio (Academic Press, 2022)
Human Orthopaedic Biomechanics: Fundamentals, Devices and Applications covers a wide range of biomechanical topics and fields, ranging from theoretical issues, mechanobiology, design of implants, joint biomechanics, regulatory issues and practical applications. The book teaches the fundamentals of physiological loading and constraint conditions at various parts of the musculoskeletal system. It is an ideal resource for teaching and education in courses on orthopedic biomechanics, and for engineering students engaged in these courses. In addition, all bioengineers who have an interest in orthopedic biomechanics will find this title useful as a reference, particularly early career researchers and industry professionals.